Repetitive negative thinking mediates the association between perfectionism and psychological distress. (January 2015) - Macedo, A.; Soares, M.J.; Amaral, A.P.; Nogueira, V.; Madeira, N.; Roque, C.; Marques, M.; Maia, B.; Bos, S.; Valente, J.; Pereira, A.T.
Highlights: Perfectionism variables are independent predictors of psychological distress (PD). Repetitive negative thinking (RNT) variables are independent predictors of PD. RNT is a partial mediator of the relationship between negative perfectionism and PD. RNT is a full mediator of the relationship between positive perfectionism and PD. Abstract: Our objective was to analyze the relationships between Repetitive negative thinking (RNT), perfectionism and psychological distress. Specifically we wanted to test if RNT mediates the relationship between perfectionism and psychological distress. 788 college students completed self-report questionnaires to evaluate perfectionism trait dimensions [Evaluative concerns (EC) and Positive strivings (PS)], RNT dimensions [Repetitive thinking (RT) and Cognitive interference and unproductivity (CIU)], perceived stress, and perceived support. Psychological distress was measured with the Profile of Mood States subscales: Depression (D), Tension–anxiety (TA), Anger–hostility (AH), Fatigue–inertia (FI) and Vigor–anxiety (VA). After controlling for perceived stress and support, perfectionism dimensions and RNT (particularly CIU) remained a significant predictors of psychological distress. CIU was a partial mediator of the relationship between EC and D, TA, AH, FI and VA and a full mediator of the relationship of PS with D and FI. Whereas the effect of negative perfectionism on emotional disturbances was potentiated by RNT, PS was only associated to it when high levels of RNT were also present. Showing that Positive striving effects on psychological distress may be a function of specific mediators, these results contribute to a better understanding of the nature of positive perfectionism.